2011
DOI: 10.24212/2179-3565.2011v2i1p2-12
|View full text |Cite
|
Sign up to set email alerts
|

Localisation Strategies of Firms in Wind Energy Technology Development

Abstract: Abstract:The paper looks at the localization strategies of multinational wind in emerging countries of China and India. It explains why these firms are localising new manufacturing and R&D facilities in countries like China and India, and how local knowledge and capabilities are being increasingly integrated into global technology and manufacturing networks of multinationals. It explores the reasons behind the localization of MNC that helps them gain strategic access to wind technological capabilities in emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The energy industry must cope with growing oil scarcity, problems of securing supply, environmental degradation, and growing needs in developing and emerging economies (Dorian et al, 2006). Global energy corporations' location strategies partially reflect such challenges (Perrot and Filippov, 2010). These companies are traditionally not incorporated in the GaWC rankings, which encompass firms that are involved in accountancy, advertising, banking/finance/insurance, legal services, and management consultancy.…”
Section: Methodsmentioning
confidence: 99%
“…The energy industry must cope with growing oil scarcity, problems of securing supply, environmental degradation, and growing needs in developing and emerging economies (Dorian et al, 2006). Global energy corporations' location strategies partially reflect such challenges (Perrot and Filippov, 2010). These companies are traditionally not incorporated in the GaWC rankings, which encompass firms that are involved in accountancy, advertising, banking/finance/insurance, legal services, and management consultancy.…”
Section: Methodsmentioning
confidence: 99%
“…In order to establish themselves in Tianjin cluster during 2005, success lured foreign firms such as Vestas, had setup a factory with a 363 million USD making it an important manufacturing base in China. Choice of selection of this cluster was due to its location and infrastructure (Perrot and Filippov, 2010). As of now, it has developed a strong value chain with 80 odd local suppliers.…”
Section: (4) Effect Of Clusters' Technological Progressmentioning
confidence: 99%
“…According to Perrot and Filippov (2011), within the renewable energy sector there was also the issue of high operational costs that characterise markets like wind and solar, and which make the markets depend on production incentives, local subsidies, and tax benefits. Thus, sustainable energy companies became attracted to the low-cost advantages and large market size in emerging Asian economies, the relatively adequate level of existing skills and facilities there, and the previous success of destination countries like Taiwan and China in the manufacture of semiconductors and microchips; the stagnation of western markets at intervals between the 1980s and the current decade further catalysed this trend (Perrot & Filippov, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another common social argument against the "internationalisation" of companies' operations is that it results in the loss of jobs in the companies' home countries (Hamilton & Summy, 2011;Alaane & Saari, 2006;Li, 2005). However, Perrot and Filippov (2011) suggested that the transfer of functions such as research and development to overseas locations is not always a "zero-sum game", as it does not by default lead to the closure of corresponding jobs in the home country. Other reasons that are attributed towards the support for localisation include rising labour costs in developing countries, rising energy costs, the export-import balance, currency depreciation, and the leaning of public attitudes towards environmental protection and social responsibility (Longo, Markandya, & Petrucci, 2008;Ristola & Mirata, 2007;Walker, 1995).…”
Section: Introductionmentioning
confidence: 99%